Health Disparities in the Immunoprevention of Human Papillomavirus Infection and Associated Malignancies - Bakir, Amira H.; Skarzynski, Martin (Frontiers in Public Health, 2015)
Human papillomavirus (HPV) causes roughly 1.6% of the plus 1.6 million cases of cancer that are diagnosed in the United States each year. Despite the proven safety and efficacy of available vaccines, HPV remains the most common sexually transmitted infection. Underlying the high prevalence of HPV infection is the poor adherence to the Centers for Disease Control recommendation to vaccinate all 11- to 12-year-old males and females. In fact, only about 38 and 14% of eligible females and males, respectively, receive the complete, three-dose immunization. The many factors associated with missed HPV vaccination opportunities – including race, age, family income, and patient education – contribute to widespread disparities in vaccine completion and related health outcomes. Beyond patient circumstance, however, research indicates that the rigor and consistency of recommendation by primary care providers also plays a significant role in uptake of HPV immunization. Health disparities data are of vital importance to HPV vaccination campaigns because they can provide insight into how to address current problems and allocate limited resources where they are most needed. Furthermore, even modest gains in populations with low vaccination rates may yield great benefits because HPV immunization has been shown to provide herd immunity, indirect protection for non-immunized individuals achieved by limiting the spread of an infectious agent through a population. However, the impact of current HPV vaccination campaigns is hindered by stagnant immunization rates, which remain far below target levels despite a slow overall increase. Furthermore, gains in immunization are not equally distributed across gender, age, demographic, and socioeconomic divisions within the recommended group of vaccine recipients. To achieve the greatest impact, public health campaigns should focus on improving immunization coverage where it is weakest. They should also explore more subtle but potentially significant determinants of HPV vaccine initiation and completion, such as the attitudes of parents and healthcare providers and factors that exacerbate HPV-related health outcomes, including smoking and human immunodeficiency virus-mediated immunosuppression. Optimizing the efficacy of vaccination campaigns will require a health disparities approach that both identifies and remedies the underlying causes of population differences in HPV vaccination.